Strengthening of masonry structures using steel frames - Papalou, Angeliki (International Journal of Engineering and Technology, 2012)
Many old masonry structures have not been maintained properly and have been left exposed to future seismic loading with only their exterior masonry walls. These structures can be strengthened using different techniques with the reversible ones being more appropriate for historic structures. The seismic behavior of masonry buildings left only with their perimeter walls and retrofitted using steel frames (a reversible technique) is investigated. The role of the connection of the steel frames with the masonry walls is analyzed. Linear elastic analysis is performed using the finite element method. The seismic resistance of the aforementioned buildings increases when there is a closed-spaced connection of the steel frame columns with the masonry walls. The connection of the masonry walls at the floor level with the interior structure is also beneficial to the building’s seismic behavior.